Extremely high birth prevalence of sickle cell disease in rural Tanzania. Issue 11 (16th August 2020) - Eastburg, Luke; Peckham, Andrew; Kawira, Esther; Chirangi, Bwire; Adler, David; Akungo, Brian Dee; Smart, Luke R.; Ambrose, Emmanuela E.
Abstract: Background/objectives: Sickle cell disease (SCD) is an important, hidden cause of childhood mortality worldwide. It is most prevalent in sub‐Saharan Africa where national newborn screening programs remain unavailable and most children in rural areas are never diagnosed. We conducted a study at a rural district hospital in northern Tanzania to determine the birth prevalence and community awareness of SCD and to determine the feasibility of using point‐of‐care testing to enroll newborns in a new SCD clinic for ongoing treatment. Design/methods: We screened infants at Shirati KMT hospital for SCD using HemoTypeSC, an inexpensive point‐of‐care test. Infants who screened positive were enrolled in the SCD clinic and instructed to return at 6‐12 weeks for confirmatory testing, counseling, and preventive care. Results: A total of 999 newborns were screened from February to September 2019. Among these, 31.6% (315/999) had sickle cell trait and 3.9% (39/999) had SCD. No hemoglobin C was detected. Very few parents knew their own sickle cell status (0.3%). At 5 months after completion, 12 infants from the screening study and 30 additional children had been seen at the SCD clinic for ongoing counseling and care. Conclusions: Birth prevalence of SCD in rural Tanzania is extremely high and community awareness is low. Newborn point‐of‐care testing enhances case finding and enables early enrollment in preventive care for SCD, even in rural sub‐Saharan Africa with minimal laboratory capacity. SCD‐specific clinical services implemented at the district hospital level could expand access to many children and significantly reduce early SCD morbidity and mortality.